POTENSI TEKNOLOGI ASAP CAIR TEMPURUNG KELAPA TERHADAP KEAMANAN PANGAN - Longa Rasi, Antonius Juandri; Seda, Yulius Prianto; Abrina Anggraini, Sinar Perbawani (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Liquid smoke is a chemical derived from the condensation of smoke decomposition of organic compounds in the process pirolosis. Liquid smoke contains several components that support the properties and functional. Many liquid smoke contains a number of chemical compounds that have the potential as a raw material of food preservatives. Liquid smoke used for food preservative must be free of dangerous compounds such as polycyclic aromatic hydrocarbons. Based on the quantity, liquid smoke coconut shell can produce the greatest yiel data temperature of 400â to produce a yield of 11.83 (%w/w). Based on the quality, liquid smoke coconut shell has a very good quality at a temperature of 400â with a total yield of 11.83 (%w/w), a pH value of 1.23, and a phenol content of 4.63%. This shows that the liquid smoke has excellent antibacterial properties, liquid smoke plays an important roleas a giver of good aroma and antioxidant as well as a distinctive flavor in food products. Liquid smoke coconut shell can also be used as a preservative safe alternative to konsumsi. This is evidenced by the detection of compound benzo (a) pyrene in smoked grade 1 Kata kunci : asap cair, proses pirolisis, benzo (a) pirene